The relationship between the ability to identify the subject-verb agreement and to write complex sentences among the second grade students of the state senior high school 1 Bantul in the academic year of 2003/2004 / Ika Frida Wulandari - IKA Frida Wulandari; ABDUL Ghani Johan (Universitas Negeri Yogyakarta, 2005)
xiii, 74 lembar ; 29,5 cm